2015
DOI: 10.1167/iovs.15-17629
|View full text |Cite
|
Sign up to set email alerts
|

MonoallelicABCA4Mutations Appear Insufficient to Cause Retinopathy: A Quantitative Autofluorescence Study

Abstract: This study indicates that carriers of monoallelic ABCA4 mutations are phenotypically normal. However, biochemical analysis in the Abca4-deficient mouse model suggests detectable effects of one mutation in ABCA4 on the molecular level. The findings may have implications for therapeutic approaches such as gene replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…1 These numbers are comparable to those in the studies by Burke et al 6 (~20%) and Fishman et al, 8 in which approximately 30% of patients presented with the absence of dark choroid on fluorescein angiography. It is also worth stressing that qAF values change with the disease stage so that very advanced patients with large areas of atrophy have lower qAF values, probably due to the absence of RPE (and photoreceptor) cells.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…1 These numbers are comparable to those in the studies by Burke et al 6 (~20%) and Fishman et al, 8 in which approximately 30% of patients presented with the absence of dark choroid on fluorescein angiography. It is also worth stressing that qAF values change with the disease stage so that very advanced patients with large areas of atrophy have lower qAF values, probably due to the absence of RPE (and photoreceptor) cells.…”
supporting
confidence: 84%
“…It is also worth stressing that qAF values change with the disease stage so that very advanced patients with large areas of atrophy have lower qAF values, probably due to the absence of RPE (and photoreceptor) cells. 6 Third, Müller et al 1 Fourth, the authors try to explain the increased qAF in one of the carriers by ''another, mild ABCA4 allele,'' rendering that individual not a heterozygous carrier but rather one an affected by STGD1 due to compound heterozygosity. However, the allele under question, p.Asn1868Ile, is a well-known common variant with the allele frequency of 7% in the general population of European descent (ExAC database; http://exac.…”
mentioning
confidence: 99%
“…As elevated FAF intensity is the first measurable change in STGD1, 55 the innovative in vivo imaging modality of quantitative FAF appears to be more suitable in this particular context. [56][57][58][59] In AMD, the distinct alterations of the CC flow signal texture outside of atrophy might potentially be indicative of choroidal alterations beyond the area of complete RPE atrophy. A longitudinal comparison of these OCT-A alterations with the established FAF characteristics as prognostic determinants seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…63 Regarding FAF, STGD1 may often be easily identified based on characteristic phenotypic features such as flecks, peripapillary sparing, and elevated FAF intensity. [55][56][57][58][59]61,64 In contrast, AMD reveals different FAF patterns and low to low-normal FAF intensity. 61,65 While good diagnostic separability is given for STGD1 and AMD based on FAF imaging and genetic testing, the study presented here outlines a framework that may now be used for subphenotype analysis within disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of healthy eyes with this novel methodology has demonstrated that quantitative FAF parameters increase with age and are higher in women and may vary with ethnicity. This modality has increasingly been used to study eyes with retinal dystrophies, such as Stargardt disease [27][28][29] and may be useful for studying areas of advanced and nascent atrophy in AMD, 31 although further efforts are needed to validate its utility for this disease.…”
Section: Quantitative Autofluorescencementioning
confidence: 99%